2013
DOI: 10.11646/zootaxa.3666.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the comb-footed spider subfamily Spintharinae (Araneae, Araneoidea, Theridiidae), with generic diagnoses and a key to the genera

Abstract: The monophyly of Spintharinae is supported in agreement with previous analysis of Theridiidae by Agnarsson and Arnedo et al. We study the relationships of the genera within Spintharinae. Fourteen species in the genera Chrosiothes, Episinus, Spintharus, Stemmops, and Thwaitesia constituted the ingroup, while five species from the genera Euryopis and Dipoena (Hadrotarsinae), as well as Latrodectus and Steatoda (Latrodectinae), served as outgroup taxa. The character matrix included 49 morphological characters. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(41 reference statements)
1
6
0
1
Order By: Relevance
“…1A), with sticky globules near substrate (Eberhard et al, 2008). See Hentz (1850), Levi (1954aLevi ( , 1963a and Durán-Barrón et al (2013) for additional descriptions and diagnoses.…”
Section: Spintharus Hentz 1850mentioning
confidence: 99%
See 2 more Smart Citations
“…1A), with sticky globules near substrate (Eberhard et al, 2008). See Hentz (1850), Levi (1954aLevi ( , 1963a and Durán-Barrón et al (2013) for additional descriptions and diagnoses.…”
Section: Spintharus Hentz 1850mentioning
confidence: 99%
“…The genus was present in the higher-level phylogenetic analyses of Agnarsson (2004) based on morphology, and the molecular studies of Arnedo et al (2004) and Liu et al (2016). An analysis of morphological data, focusing on spintarines, was then presented by Durán- Barrón, Rosas & Contreras-Ramos (2013). These studies have strongly supported the monophyly of Spintharinae, but do not agree on the exact placement of Spintharus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genera Spintharus, Thwaitesia, and Episinus all tend to build an H-shaped web with the animal facing downwards and holding onto parts of the web with its feet, presumably specializing on pedestrian prey such as ants (Agnarsson 2004;Eberhard et al 2008). A close relationship between Thwaitesia and Epsisnus was proposed by Durán-Barron et al (2013) based on morphology. However, also based on morphology, Rodrigues et al (2022), found that Thwaitesia is unrelated to Episinus, and morphological evidence showed that humps are present on the abdomen in Episinus but absent in Thwaitesia.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de não haver um valor padrão de k, e sua escolha parecer arbitrária entre cada autor, ainda é preferível valores baixos, principalmente entre k=1 e k=10 (Goloboff, 1993;Goloboff et al, 2008;Ramírez, 2003;Agnarsson, 2004;Arnedo et al, 2009;Frick et al, 2010;Mendes, 2011;Durán-Barrón et al, 2013;Gavish-Regev et al, 2013;Frick & Scharff, 2013). No entanto, neste estudo, para explorar os resultados desses valores de k, e tentar obter variados parâmetros para testar a estabilidade dos clados, foram estipulados para constante k=1- 15,20,25,30,35,40,45, 50 e 100.…”
Section: Análise Cladísticaunclassified